2003
DOI: 10.1051/0004-6361:20030660
|View full text |Cite
|
Sign up to set email alerts
|

Trends in E2 and M1 transition rates between 3p${_{{\mathsf{3/2}}}}$ and 3p${_{\mathsf{{1/2}}}}$ levels in 3s${^{\mathsf{2}}}$ 3p${^k}$ systems

Abstract: Abstract. The analysis of forbidden lines, such as E2 and M1, in the atomic spectra emitted by certain ions is important for the study of the plasma in astrophysical objects and fusion devices. Transition rates between 3p 3/2 and 3p 1/2 levels in 3s 2 3p k ions that belong to the aluminium sequence have been calculated with the Relativistic Quantum Defect Orbital (RQDO) method. The present data are tested by comparison with other theoretical data available in the literature, and the regularity of the transitio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2007
2007
2025
2025

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 28 publications
1
12
0
Order By: Relevance
“…On the basis of the accuracy of the results obtained previously with the same method for other homologous sequences with 2p and 3p valence configurations [14,15], and in view of the smooth behaviour observed along these two sequences, the present set of results may also be expected to be accurate. Experimental transition probabilities or f -values would, however, be required to estimate the uncertainties in the data reported here.…”
Section: Discussionsupporting
confidence: 56%
See 2 more Smart Citations
“…On the basis of the accuracy of the results obtained previously with the same method for other homologous sequences with 2p and 3p valence configurations [14,15], and in view of the smooth behaviour observed along these two sequences, the present set of results may also be expected to be accurate. Experimental transition probabilities or f -values would, however, be required to estimate the uncertainties in the data reported here.…”
Section: Discussionsupporting
confidence: 56%
“…The values for the transition rates via the electric quadrupole (E2) and magnetic dipole (M1) mechanisms are shown in Figures 2 and 3, respectively. The RQDO A-values plotted for B and Al-like ions have been taken from Charro et al [14,15].…”
Section: Regularities In Homologous Seriesmentioning
confidence: 99%
See 1 more Smart Citation
“…Feldman et al (1991Feldman et al ( , 2001 and Doron and Feldman (2001) performed a systematic study of densitysensitive magnetic dipole lines in Ti-like ions including W 53+ . Relativistic quantum defect orbital (RQDO) calculations of transition rates for electric quadrupole and magnetic dipole lines for ions along the potassium and aluminium isoelectronic sequences, including W 55+ and W 61+ , were carried out by Charro et al (2002Charro et al ( , 2003, respectively. Atomic structure and radiative properties of forbidden transitions in Yb-like, Aglike, Zn-like, Ca-like, Al-like, Mg-like, B-like and Be-like Ion Label jj designation (10 3 cm −1 ) (10 3 cm −1 ) and W 70+ , were computed with the relativistic many-body perturbation theory (RMBPT) by Safronova and Safronova (2010).…”
Section: Introductionmentioning
confidence: 99%
“…Lavin et al reported theoretical oscillator strengths for 3s 2 3p 2 P-3s 2 3d 2D, 3s 2 3p 2 P-3s 2 4s 2 S and 3s 2 4s 2 S-3s 2 4p 2 P using the quantum defect orbital method (QDO) and its relativistic counterpart (RQDO) [14]. Charro et al analysed the trends in E2 and M1 transition rates between 3p 3/2 and 3p 1/2 levels in 3s 2 3p k systems using RQDO method [15]. Safronova et al displayed a computation of relativistic many body calculations of electric-dipole properties for n=3 in Al-like ions [16].…”
Section: Introductionmentioning
confidence: 99%